THE THING ABOUT RELIGIOUS RITES AND PERFORMANCES - Henyei Neto, Gyorgy (Último Andar, 2015)
The objective of this paper is to provide with new insights the discussion of anthropological questions of religion, focusing on the roles of myths and rituals on the human relationship with the environment, culture and heritage. By providing a deconstruction of concepts such as myths of creation and ritualistic performances, this work will discuss this human behaviours in spaces not primordially designated for sacred enactments. During the discussion, examples of ritualistic acts in public spaces will arise, mostly based on events occurred in museums and art exhibitions.